The emotionally intelligent leader - Goleman, Daniel (Boston Harvard Business Review Press, 2019)
Bestselling author DANIEL GOLEMAN first brought the concept of emotional intelligence (EI) to the forefront of business through his articles in Harvard Business Review, establishing EI as an indispensable trait for leaders. The Emotionally Intelligent Leader brings together three of Goleman's bestselling HBR articles.
Includes index.
Keywords: Leadership